Securing The Border: Examining The Interagency Border Control Management in Kedah and Perlis (S/O 13762) - Ahmad Apandi, Laila Suriya; Omar, Rusdi; Anuar, Abdul Rahim; Abdullah, Mohd Kamarulnizam; Yaacob, Che Mohd Aziz (UUM, 2021)
The study aims to examine the inter-agency cooperation within the framework of border control management in Kedah and Perlis. Its research questions are: (a) To what extent does the inter-agency cooperation affect effectiveness of border control management in Kedah and Perlis? What are the issues of inter-agency cooperation with reference to the border control management in Kedah and Perlis? What are the challenges that inter-agency cooperation faced when securing the border between Malaysia and Thailand? To address these questions, the study employed adopted qualitative research by conducting newspaper analysis, focus group discussion, and in-depth interviews with elites. The study found that inter-agency cooperation affects the effectiveness of border control management in Kedah and Perlis. In particular, issues and challenges of inter-agency cooperation affect the effectiveness of border control management in Kedah and Perlis. The opening eye incident of deadly human trafficking camp and mass graves in Wang Kelian has prompted the government of Malaysia to take drastic action by establishing Malaysian Border Security Agency (AKSEM) in November 2015. It is fair to say much improvement has been done with the establishment of AKSEM in terms of coordinating inter-agency cooperation, resources, and institutional capacity. However, challenges in the forms of external factors have not been addressed accordingly, notably the rat trails/holes and existing fencing along the border of Malaysia and Thailand.